BENTUK LAGU MARS FKIP UNIVERSITAS PGRI PALEMBANG IRINGAN MUSIK FORMAT ORKESTRA - Siswanto, Silo (UNIVERSITAS INDO GLOBAL MANDIRI)
AbstractThe motto of PGRI Palembang University is that the campus advances with quality. Then a need for faculties to make a stragi in providing encouragement and motivation to the academic community to carry out the tri dharma of higher education. (FKIP) Palembang PGRI University through its highest leadership in the faculty gave a letter of assignment to work on the Mars song FKIP PGRI Palembang University to one of the music art lecturers in the performing arts education study program named Silo Siswanto, M.Sn. Then the Mars song was finished on July 23, 2018 and was launched on July 31, 2018 in the FKIP University of Palembang PGIP judicial event held at the Science Center building at the PGRI University in Palembang. Regarding the form in the Mars song, of course, this song has pieces of melody that are often known by the term phrases or musical sentences that make up the song. while the accompaniment music is arranged in an orchestra format. The formulation of the problem. (1) What is the form of Mars FKIP University PGRI Palembang song. (2) How is the accompaniment of Mars FKIP Palembang PGRI University music with orchestra format. The results of the discussion FKIP march song has a poly metric musical form where the antecedent phrase and consequent phrase do not have the same number of bars for example period C has 9 bars consisting of the phrase d 4 bars and the phrase e 5 bars.Keywords : Song Form, Mars Song, OrchestraAbstrakMotto Universitas PGRI Palembang yakni kampus melaju dengan mutu. Maka suatu kebutuhan bagi fakultas-fakultas membuat suatu stragi dalam memberikan dorongan dan motovasi kepada civitas akademika untuk melaksanakan tri dharma perguruan tinggi. (FKIP) Universitas PGRI Palembang melalui pimpinan tertingginya di fakultas memberikan surat tugas untuk penggarapan lagu Mars FKIP Univesitas PGRI Palembang kepada salah satu dosen seni musik di prodi pendidikan seni pertunjukan bernama Silo Siswanto, M.Sn. Kemudian lagu Mars tersebut selesai dibuat tanggal 23 juli 2018 dan di launching pada tanggal 31 juli 2018 dalam acara yudisium FKIP Universitas PGRI Palembang bertempat di gedung Science Center Universitas PGRI Palembang. Mengenai bentuk dalam lagu Mars tersebut, tentunya lagu ini memiliki potongan-potongan melodi yang sering dikenal dengan istilah frase atau kalimat musik yang membentuk lagu tersebut. sedangkan musik iringannya diarransemen dengan format orkestra. Adapun rumusan masalahnya. (1) Bagaimana bentuk lagu Mars FKIP Universitas PGRI Palembang. (2) Bagaimana musik iringan lagu Mars FKIP Universitas PGRI Palembang dengan format orchestra. Hasil pembahasan Lagu mars FKIP memiliki bentuk musik poli metrik dimana frase antecedent dan frase consequent tidak memiliki jumlah birama yang sama misalnya periode C memiliki 9 birama yang terdiri dari frase d 4 birama dan frase e 5 birama.Kata kunci : Bentuk Lagu, Lagu Mars, Orkestra